Influence of Preparation Design on the Fracture Resistance of Endodontically Treated Teeth Restored with Full-Coverage Crowns in Jakarta, Indonesia - Alexander Mulya; Nabila Saraswati; Serena Jackson; Made Swastika; Zainal Abidin Hasan (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Endodontically treated teeth are more susceptible to fracture due to the loss of tooth structure and moisture. Full-coverage crowns are often used to restore these teeth and enhance their fracture resistance. However, the influence of different preparation designs on the fracture resistance of endodontically treated teeth remains a topic of investigation. This study aimed to evaluate the fracture resistance of endodontically treated teeth restored with full-coverage crowns with different preparation designs in Jakarta, Indonesia. Methods: Forty extracted human premolars were endodontically treated and divided into four groups (n=10): Group 1: Butt-joint margin with a 1 mm chamfer finish line; Group 2: Shoulder margin with a 1.5 mm chamfer finish line; Group 3: Deep chamfer margin with a 2 mm chamfer finish line; and Group 4: Shoulder margin with a rounded shoulder finish line. All teeth were prepared for full-coverage crowns and restored with standardized metal-ceramic crowns. A universal testing machine was used to apply compressive load to the teeth until fracture. The fracture resistance values were recorded in Newtons (N) and analyzed using one-way ANOVA and Tukey's post-hoc test (α=0.05). Results: The mean fracture resistance values (N) were as follows: Group 1 (1250 ± 150), Group 2 (1480 ± 180), Group 3 (1180 ± 130), and Group 4 (1550 ± 200). One-way ANOVA revealed significant differences in fracture resistance among the groups (p<0.05). Tukey's post-hoc test indicated that Group 4 exhibited significantly higher fracture resistance than Group 1 and Group 3 (p<0.05). Group 2 also demonstrated significantly higher fracture resistance than Group 3 (p<0.05). Conclusion: Within the limitations of this study, the shoulder margin with a rounded shoulder finish line provided the highest fracture resistance for endodontically treated teeth restored with full-coverage crowns. The butt-joint margin and deep chamfer margin preparations exhibited lower fracture resistance.